Cutaneous-Pericardial Fistula: Rare Complication of Transapical Aortic Valve Replacement—Case Report and Literature Review - Andrei Tarus (Case Reports in Surgery, 2020)
Cutaneous-pericardial fistula is a rare complication of transapical aortic valve replacement; only a few cases are reported in the literature. It is part of a wide range of surgical site infection manifestations that could emerge after surgery. Due to its proximity to the heart, the risk of infectious lesions of adjacent structures and inoculation of pathogens on the prosthetic valve can lead to life-threatening complications. We report here a case of successful surgical treatment through reduced ribs and soft tissue operative trauma.